TEORI PEMAIAKAIN DAN KEPUASAN - Abdullah, Abdullah (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
Blummer and katzât uses and gratification theory suggest that media usert play an cative role in choosing and using the media. UsersÂ  take an active part in the communication process and are goal oriented in ther media use. Blumer and katz say the a media user seeks out a media source that be fulfils the needs of the user. Uses and gratifications theory asssume that tge user has alterate choice to satisty their need. Empirical reserch based on uses ang grafitifcation theory in indonesia is very limetes or not yet to be done.